Coronary Artery Plaque Composition and Severity Relate to the Inflammasome in People With Treated Human Immunodeficiency Virus. (1st March 2023) - Schnittman, Samuel R; Kitch, Douglas W; Swartz, Talia H; Burdo, Tricia H; Fitch, Kathleen V; McCallum, Sara; Flynn, Jacqueline M; Fulda, Evelynne S; Diggs, Marissa R; Stapleton, Jack T; Casado, José L; Taron, Jana; et al.
Abstract: Background: Inflammasome activation is increased in people with human immunodeficiency virus (PWH), but its relationship with coronary plaque is poorly understood in this setting. Methods: In a large human immunodeficiency virus cardiovascular prevention cohort, relationships between caspase-1, interleukin (IL)-1β, and IL-18 and coronary plaque indices were assessed by multivariate logistic regression. Results: Higher IL-18 and IL-1β were associated with Leaman score, an integrative measure of plaque burden and composition. Conclusions: As Leaman score >5 is associated with cardiovascular events in the general population, future work is needed to determine how the inflammasome relates to events and whether strategies to reduce its activation affect events or plaque progression among PWH. Abstract : Among ART-treated people with HIV at low-moderate traditional cardiovascular disease risk, inflammasome activation markers were associated with Leaman score, a composite index of plaque burden and severity, which has been associated with major cardiovascular events in the general population.